The Significance of Makassar Port in the Context of Cargo Containers and Passenger Traffic: A Literature Review - Imaduddin Murdifin (Migration Letters, 2023)
The study focused on analyzing the movement of commodities, ships, and people at Makassar Port, comparing its performance with four other major ports over the past five years. This study used descriptive qualitative methods. The growth ratio approach was employed to quantify transportation development, while proportion analysis was utilized to assess Makassar Port’s significance relative to the other major ports. Analysis was utilized to assess Makassar Port’s significance relative to the other major ports. Makassar Port’s role in the overall transportation landscape of Indonesia reveals that it only handles 12.7% of incoming commodities and 10.27% of outbound transit when considering the five major ports under investigation. Despite Makassar Port’s advantageous location and substantial TEU capacity, it was found that the port predominantly facilitates the export of commodities rather than imports. Additionally, a higher volume of items is transported to and from islands for incoming cargo compared to outgoing cargo. Makassar Port plays a vital role in Indonesia’s maritime trade, its proportionate contribution to the overall transportation network is modest.